Pigmentation of regenerated hairs after wounding. Issue 1 (October 2016) - Yuriguchi, Minoru; Aoki, Hitomi; Taguchi, Nobuhiko; Kunisada, Takahiro
Highlights: ⿢ Regeneration of pigmented hairs was attained by creating a skin wound in anagen. ⿢ Wnt7a expression in1st anagen skin is likely to activate melanocytes. ⿢ Kitl activated melanocytes also facilitates the pigmented hair regeneration after wounding. Abstract: Background: After severe wounding, hair follicles were known to be regenerated de novo along with the re-epithelialization. However, the regenerated hairs lack pigmentation. Objective: We aimed to find out the condition to regenerate pigmented hairs after severe wounding. Methods: De novo hair regeneration was observed during the re-epithelialization process after the full thickness excision of dorsal skin. Hair pigmentation mechanism was assessed by the modulation of Wnt and Kit signalings. Results: Stable regeneration of pigmented hairs was demonstrated when a wound was created to the mice during the anagen stage of the hair cycle. A significant increase in the number of melanocyte stem cells in the postnatal 1st anagen interfollicular skin of 5-week-old mice was observed. An increase of Wnt7a of the keratinocytes was observed in the skin at this stage, which may direct melanocyte stem cells to produce pigmented hairs in the regenerating follicles. This was supported by the finding that transgenic mice expressing the melanocyte stimulatory factor Kitl in their skin promoted the regeneration of pigmented hairs irrespective of the stage of the hair cycle. Conclusion: Our results provide a new insight into the intimate regulation process between two follicular stem cell systems, keratinocyte stem cells and melanocyte stem cells, during de novo hair regeneration after wounding.